W poszukiwaniu mistrza i autorytetu duchowego. Ojciec Jacek Woroniecki OP we wspomnieniach współbraci zakonnych, uczniów i przyjaciół - Miławicki, Marek (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Dominican Father Jacek Woroniecki (1878–1949) was one of the greatest Polish thinkers and priests in the first half of the twentieth century. An outstanding professor, rector of the Catholic University of Lublin and a priest, he was also a famous lecturer, pastor and educator of Polish Catholic intellectuals. He was a spiritual master and authority for many people. This article attempts to show the characteristics that Woroniecki had through which a lot of people – students, professors, politicians and clergy (including bishops) – considered him their mentor. The recollections of these people were used to describe his features of personality. Even today his texts can inspire, and his attitude could be a role model for contemporary teachers and educators.
Keywords: Association of Catholic University Students; authority; Catholic University of Lublin; Dominican order; Jacek Woroniecki; ministry; Odrodzenie; recollections